Analisis Tingkat Penerimaan E-Learning Sebagai Alternatif Media Pembelajaran Pada Siswa SMK - Faizatul Amalia; Rizki Tri Sulistyo; Adam Hendra Brata (SMATIKA JURNAL : STIKI Informatika Jurnal, 2020)
A learning system that used the internet to make learner can learn is called with e-learning. Almost in every learning process, e-learning already has been implemented. However, the usage of e-learning shall be found out from the students perspective especially in Vocational School in one of a city from Indonesia beside the usage of module. So that, the research is designed with the Technology Acceptance Model (TAM). The survey is used as a methodology in this research. The object of this research is all students in Vocational School in Malang which is 32,802 in 2018. With the population, the researcher uses the sampling technic to get the proportional sample of students using purposive random sampling. Application of the TAM in this research shows result as percentage in every variables are: (1) e-learning self-efficacy has 84.68% which is very high category; (2) complexity has 46.79% which is in moderate category; (3) lack of time has 59.42% which is in a high category; (4) perceive usefulness has 87.2% which is in very high category; (5) perceived ease of use has 80.90% which is in very high category; (6) behavioral intention to use has 81.98% which is in the very high category; (7) actual technology use has 69.31% which is in the high category. From the result, some factors affect the usage of e-learning for the learner in the learning process. The factors are: (1) e-learning self-efficacy as a pretension to seek information from e-learning; (2) complexity to use the e-learning system; (3) lack of time to use e-learning beside learning process in class and extra activity in school; (4) the benefit perception of using e-learning in daily learning process; (5) easily perception to use e-learning. The fifth factors make students to use e-learning to assign their task and this will make students use in their daily learning process.